IMPLIKASI KETERLAMBATAN PERPANJANGAN SURAT IJIN PRAKTIK TENAGA MEDIS DALAM PELAYANAN KESEHATAN - Ai Uuh Muhlasoh; Mery Herlina; Dede Permana (Jurnal Penelitian Hukum Galunggung, 2025)
This research is motivated by the importance of a Practice Permit (SIP) as the legal and administrative basis for medical personnel to legally provide health services to the public. According to Law Number 17 of 2023 concerning Health, a SIP is valid for five years and must be renewed before it expires. Delays in the SIP renewal process can result in medical personnel being deemed illegal in their practice, which can lead to termination of services and the threat of legal and administrative sanctions. The purpose of this study is to determine and analyze the impact of delays in SIP renewal on health services and to identify obstacles and efforts made by medical personnel in the process, specifically at Jasa Kartini Hospital in Tasikmalaya City. The research method used is empirical juridical, namely a combination of a normative approach and empirical observation in the field. The results show that the main obstacles in SIP renewal include technical issues with the online system, complex administrative requirements, lack of socialization, and high workloads. Suggested solutions include early renewal applications, digitization of required documents, technical training, and improving complaint services from relevant agencies. This study emphasizes the need for reform of the licensing system to ensure the continuity of fair, effective, and legal health services.